Proceedings of the Ocean Drilling Program, 157 Scientific Results 1998
DOI: 10.2973/odp.proc.sr.157.100.1998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seismic reflection data to a synthetic seismogram in a volcanic apron at Site 953

Abstract: The volcanic apron of Gran Canaria at Site 953 is characterized by numerous, closely spaced reflectors, allowing a highresolution stratigraphic correlation. The calibration of the presite survey seismic data (during the Meteor Cruise 24) with regard to the lithology and stratigraphy found at the drill site was achieved by computing a synthetic seismogram serving as the link between seismic and borehole data. Because logging data were available for only 53% of the hole, velocity and density measurements taken f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…We thus present depth‐converted maps (Figure S1 in the supporting information) using a range of seismic velocities from 2,000 m/s to 4,000 m/s within the sediment. A seismic velocity of 2,000 m/s is comparable to the P wave velocities measured at Site 953 in the volcaniclastic apron offshore Gran Canaria (e.g., Funck & Lykke‐Andersen, ) and in the Lesser Antilles (e.g., Le Friant et al, ). For the thickness of the seismostratigraphic units, there is a linear relationship between the TWT time and the figure in meters.…”
Section: Depth Variations Of the Horizons And Thickness Mapssupporting
confidence: 62%
“…We thus present depth‐converted maps (Figure S1 in the supporting information) using a range of seismic velocities from 2,000 m/s to 4,000 m/s within the sediment. A seismic velocity of 2,000 m/s is comparable to the P wave velocities measured at Site 953 in the volcaniclastic apron offshore Gran Canaria (e.g., Funck & Lykke‐Andersen, ) and in the Lesser Antilles (e.g., Le Friant et al, ). For the thickness of the seismostratigraphic units, there is a linear relationship between the TWT time and the figure in meters.…”
Section: Depth Variations Of the Horizons And Thickness Mapssupporting
confidence: 62%
“…Geophysical logging at DSDP site 397 showed a significant acoustic impedance contrast between volcanic components and both the margin (generally quartz and feldspar) and biogenic deposits (Funck & Lykke‐Anderson 1998). Discrete volcanic layers are therefore potentially good seismic reflectors provided they are thick enough (as a rule of thumb a thin layer needs to be of the order of one thirtieth of a wavelength to be detected—for 10–20 Hz typical of deep seismic data this is equivalent to a few metres).…”
Section: The Canary Islands and Their Geological Settingmentioning
confidence: 99%
“…The reflectivity is generally higher in the northern basin. Funck and Lykke-Andersen (1998a) showed that most reflectors in the northern basin are the result of volcaniclastic material derived from the islands showing a large impedance contrast to the hemipelagic background sedimentation. The lower reflectivity in the southern basin indicates a lower amount of volcaniclastic material in this basin, an interpretation supported by drilling (Schmincke et al 1995).…”
Section: Discussionmentioning
confidence: 98%